Understanding Lexical Choices: A Linguistic Analysis of the Metatah Ritual in Menyali Village - Natih, Made Sarasvati Wirapuspa; Budasi, I Gede; Rismadewi, Ni Wayan Monik (Lexeme : Journal of Linguistics and Applied Linguistics, 2025)
The rapid development of the era impacts the sustainability of language and culture, including the lexicons in Balinese rituals. The young generation's indifference to using lexicons will result in language death which can threaten the community's cultural identity. However, studies on the lexicons used in Balinese rituals, particularly the tooth-filing ritual (Metatah), remain limited. While some research has explored the ritual's procedures, there is still a gap in identifying and analyzing the specific lexicons used. This study aims to identify the lexicons used in the procedures of the Metatah ritual in Menyali Village and analyze the cultural meaning of the identified lexicons. The ethnolinguistic perspective is used to examine the relationship between language and culture. This study was used a qualitative descriptive design. Observation and interviews with three selected informants were conducted to collect the data. The instruments used in this study were the researcher, observation sheets, interview guides, interview sheets, smartphones, and notebooks. This study employed an interactive data analysis model, consisting of three stages: data reduction, data presentation, and conclusion drawing or verification. The study results show that the Metatah ritual consists of ten procedures, with a total of thirty-five (35) lexicons used in all of these procedures. These lexicons represent the activities, tools, materials, and offerings involved in the ritual. The obtained lexicons carry cultural meanings that reflect the traditions and beliefs of the Menyali people, connected to the concept of Tri Hita Karana. The findings of this study underline the importance of maintaining the lexicons in the Metatah ritual as a source of cultural knowledge to maintain a community's identity. Thus, this study can have implications in linguistic studies as an effort to preserve the Balinese language.